Analysis of motivational factors students of management to learn (by example of bachelors of direction 38.03.02 "Management" of the faculty of management SFU) ("Journal "U". Economy. Management. Finance.", 2017)
This article is devoted to theoretical review of the content of the category of motivation, as well as the factors shaping it. Special attention has been paid to the motivational component for students in the learning process. As the applied component of the article, on the basis of the survey, analyzed the motives of the students of bachelor direction 38.03.02 "Management" of the faculty of management SFU to study.
Keywords: motivation; need; motivation to learn; motivational factors